Cash Receipt and Disbursement System on Micro Small and Medium Enterprises - Yusac Lasmana; Galih Fajar Muttaqin; Dabella Yunia (PT. EQUATOR SINAR AKADEMIA, 2022)
The purpose of this final project is to determine the system of cash receipts and disbursements in CV. BERDJUANG. The method used in writing this final project is descriptive method. This writing uses primary data and secondary data obtained from CV. BERDJUANG. The data source comes from internal data. How to collect data through observation, interviews, and documentation collected from CV. BERDJUANG.Based on final project research, the cash receipt system in CV. BERDJUANG is good, it's just that there is no petty cash. Cash disbursement system on CV. BERDJUANG is good enough, it's just that there are often errors in the calculation of money with cash records, but it has been resolved by the company's leaders.